2021
DOI: 10.1002/glia.24063
|View full text |Cite
|
Sign up to set email alerts
|

IL‐17 signaling induces iNOS+ microglia activation in retinal vascular diseases

Abstract: Activation of microglia and inflammation-mediated vascular damages are suggested to play a decisive role in the pathogenesis of various retinopathies. The inducible nitric oxide synthase (iNOS) was required for activated microglia-mediated injuries.However, the induction mechanism of microglia activation during retinal vascular diseases is still elusive. Here we showed that IL-17 induced microglia activation with high expression of iNOS and promoted the development of retinal vascular diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 52 publications
1
14
0
Order By: Relevance
“…One study suggests that CRS may decrease the size of cerebral vessels and increases blood-brain barrier (BBB) permeability, which eventually promotes leakage of plasma immunoglobulins across the BBB into perivascular and parenchymal spaces [ 55 ]. We have reported that repeated social defeat stress could induce microglia activation [ 1 ], which subsequently causes cerebrovascular inflammation [ 56 , 57 ]. In addition, mental stress is found to elevate levels of circulating proinflammatory cytokines and glucocorticoids, which potentially impacts the brain vessels by altering the central inflammatory state via glucocorticoid feedback to the brain [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…One study suggests that CRS may decrease the size of cerebral vessels and increases blood-brain barrier (BBB) permeability, which eventually promotes leakage of plasma immunoglobulins across the BBB into perivascular and parenchymal spaces [ 55 ]. We have reported that repeated social defeat stress could induce microglia activation [ 1 ], which subsequently causes cerebrovascular inflammation [ 56 , 57 ]. In addition, mental stress is found to elevate levels of circulating proinflammatory cytokines and glucocorticoids, which potentially impacts the brain vessels by altering the central inflammatory state via glucocorticoid feedback to the brain [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have confirmed that intercellular adhesion molecule-1 mediates the migration of Th17 cells in human retinal vascular endothelial cells ( 44 ). The co-staining of IL-17, RORγt and CD4 in the retina of diabetic retinopathy showed that Th17 cells infiltrated and damaged the retina during the formation of DR ( 45 ). The above results are consistent with the top five GO functional enrichment results in this study: the top five terms enriched by DETh17RGs in this study are all related to cell movement, migration and regulation.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, cluster 1 samples interact with microglia through IL17, VEGF, and POSTN, or with macrophage through TNFSF12, or with CD8 T cells through F2R more active than cluster 2 samples. IL17 can activate microglia ( 70 , 71 ) and promote GBM progression ( 72 , 73 ). The connection between POSTN and regulating TGF-β1, HIF-1α, and VEGFA expression has been confirmed, which can affect GBM progression and macrophages ( 74 , 75 ).…”
Section: Discussionmentioning
confidence: 99%